1999
DOI: 10.1074/jbc.274.30.21200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Vasopressin Prohormone Involved in Diabetes Insipidus Impair Endoplasmic Reticulum Export but Not Sorting

Abstract: Familial neurohypophysial diabetes insipidus is characterized by vasopressin deficiency caused by heterozygous expression of a mutated vasopressin prohormone gene. To elucidate the mechanism of this disease, we stably expressed five vasopressin prohormones with a mutation in the neurophysin moiety (NP14G3 R, NP47E3 G, NP47⌬E, NP57G3 S, and NP65G3 V) in the neuroendocrine cell lines Neuro-2A and PC12/PC2. Metabolic labeling demonstrated that processing and secretion of all five mutants was impaired, albeit to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
57
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 43 publications
10
57
0
Order By: Relevance
“…Expression of a number of I neurohypophysial DI constructs in cultured cells showed that all resulted in retention of mutant vasopressin prohormone in the endoplasmic reticulum (Siggaard et ul. 1999;Nijenhuis et al 1999), with structural disruption of the endoplasmic reticulum when neuro2a cells were used (Nijenhuis et al 1999). These findings support the hypothesis that a defect in intracellular transport is the underlying defect in familial neurohypophysial DI, and that prior neuronal death is not required for development of the diabetes insipidus phenotype.…”
Section: F D Grantsupporting
confidence: 76%
“…Expression of a number of I neurohypophysial DI constructs in cultured cells showed that all resulted in retention of mutant vasopressin prohormone in the endoplasmic reticulum (Siggaard et ul. 1999;Nijenhuis et al 1999), with structural disruption of the endoplasmic reticulum when neuro2a cells were used (Nijenhuis et al 1999). These findings support the hypothesis that a defect in intracellular transport is the underlying defect in familial neurohypophysial DI, and that prior neuronal death is not required for development of the diabetes insipidus phenotype.…”
Section: F D Grantsupporting
confidence: 76%
“…Mutations affecting the AVP-NPII gene are predicted to determine cytotoxic accumulation of the prohormone in the supraoptic and paraventricular nuclei, ultimately leading to neuronal damage. The expression of mutations causing adFNDI in cell models supports this hypothesis, because the mutant AVP prohormone was constantly found to be retained in the endoplasmic reticulum (11)(12)(13)(14)(15)(16)(17). More recently, these observations have been confirmed in transgenic animals expressing a mutated AVP-NPII gene (18 -20).…”
Section: Introductionsupporting
confidence: 67%
“…performed functional analyses of fi ve mutations in the AVP gene, three of them in glycine residues (G45R, G96V and G88S, respectively NP14G, NP65G and NP57G positions on neurophysin). The analyzes of mutation G88S displayed a relatively effi cient processing and secretion of protein, an aberrant distribution of the mutant prohormone within the endoplasmic reticulum (ER) and a modifi cation in ER distribution in cells (13). Therefore, they propose that the accretion and the consequent disturbance of the ER are deleterious to the cell and will decrease the functionality and/or the viability of the magnocellular neurons, which express high amounts of vasopressin prohormone in vivo (13).…”
Section: Familial Diabetes Insipidus Due To Avp Mutationmentioning
confidence: 99%
“…The analyzes of mutation G88S displayed a relatively effi cient processing and secretion of protein, an aberrant distribution of the mutant prohormone within the endoplasmic reticulum (ER) and a modifi cation in ER distribution in cells (13). Therefore, they propose that the accretion and the consequent disturbance of the ER are deleterious to the cell and will decrease the functionality and/or the viability of the magnocellular neurons, which express high amounts of vasopressin prohormone in vivo (13). This hypothesis would explain both the dominant inheritance of human adFN-DI and the delayed onset of the symptoms, as observed in some patients here described.…”
Section: Familial Diabetes Insipidus Due To Avp Mutationmentioning
confidence: 99%
See 1 more Smart Citation